تجربة بناء نظام تصنیف خاص لموضوعات التربیة الریاضیة بالاستعانة بتصنیف الكولون للرسائل الجامعیة العراقیة لمكتبة كلیة التربیة الریاضیة – جامعة بغداد (Journal of the College of Education for Women, 2019)
This research aims to find a proper way to organize the theses of thephysical education college’ s Library – Baghdad University , this is done byapplying a classification system which depends on analyzing a building aclassification number as Colon classification system , to help the classifier tosimplify and speed the procedure of building a classification number , this isdone by knowing the physical education subjects and subdivide them to theirprimary and giving them a proper symbols that describes the subject .